Optimization of fermentative hydrogen production from palm oil mill effluent in an up-flow anaerobic sludge blanket fixed film bioreactor - Mohammadi, P.; Ibrahim, S.; Annuar, M.S.M.; Khashij, M.; Mousavi, S.A.; Zinatizadeh, A.A. (Elsevier, 2017)
Response surface methodology with a central composite design was applied to optimize fermentative hydrogen production from palm oil mill effluent (POME) in an upflow anaerobic sludge blanket fixed film reactor. In this study, the concurrent effects of up-flow velocity (Vup) and feed flow rate (QF) as independent operating variables on biological hydrogen production were investigated. A broad range of organic loading rate between 10 and 60 g COD L−1 d−1 was used as the operating variables. The dependent parameters as multiple responses were evaluated. Experimental results showed the highest value of yield at 0.31 L H2 g−1 COD was obtained at Vup and QF of 0.5 m h−1 and 1.7 L d−1, respectively. The optimum conditions for the fermentative hydrogen production using pre-settled POME were QF = 2.0–3.7 L d−1 and Vup = 1.5–2.3 m h−1. The experimental results agreed very well with the model prediction.